THE APPLICATION OF BHAVANA 4 IN THE WAY OF LIFE OF BAN LA PHO COMMUNITY, PA RAI SUB-DISTRICT, MAE LAN DISTRICT PATTANI PROVINCE - Katapunyo (Chaiyawong), Phraathikankhati; ., Phrakru Kositwattananukul; Panasree , Sitthichok (Journal of MCU Nakhondhat, 2023)
The objectives of this research article were to 1) to study concept of Ban Lapoh community’s lifestyle, Banrai Subdistrict, Pattani Province. 2) to investigate Bhavana principle in Theravada Buddhist scriptures and 3) to apply the Bhavana principle in Ban Lapoh community’s lifestyle, Banrai Subdistrict, Pattani Province. This is qualitative research focusing on documentary study and in-depth- interview and presentation in descriptive form. Findings were as follows: 1) Regarding lifestyle in Ban Lapoh, Banrai Subdistrict, Pattani Province, it was found that Ban Lapoh community is the community with multiculture as Buddhists and Muslims live together as farmers, government officials, self-employed and general contractors. 2) Regarding Bhavana principle, it was found that the Bhavana principle is Buddhadhamma that can bring peace and harmony to community and lead community to be disciplined, living in social order and stable with virtue. Problem solving can be solved by using the right wisdom, and in the future the community will be living peacefully and harmoniously. 3) With regard to the application of the Bhavana principle in Ban Lapoh, Banrai Subdistrict, Pattani Province, it was found that the application of the Bhavana principle in lifestyle can lead to better development both family and society in a positive and peaceful way.